การเตรียมแผ่นฟิล์มไฮโดรเจลที่มีอนุภาคเงินนาโน : รายงานการวิจัยฉบับสมบูรณ์ - กนกวรรณ แสงเกียรติยุทธ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
Antimicrobial hydrogel films are successfully prepared by casting the mixed solutions of carboxymethylcellulose, polyethyleneglycol, polyvinylpymolidone and silver nitrate using citric acid as a crosslinking agent. Then this solution is dried and cured to generate the polymer films. The analytical results from infrared spectroscopy (IR), water absorption, solubility and mechanical property reveal that not only the cross-links between carboxymethylcellulose and citric acid are created in the films but there are also interactions between polyvinylpyrrolidone and citric acid. Additionally, increasing of polyethylene glycol content can improve the water absorption ability of the hydrogel films. The formation silver particles (Agͦ) in the gels caused by the reduction of silver ions (Ag⁺) can be readily verified by UV-Vis spectroscopy. It can be noticed that the presence of silver particles significantly decreases the water absorption ability and the film strength. Nonetheless, the films containing 5,000 ppm and 10,000 ppm of silver particles exhibit high antimicrobial activity against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Interestingly, the cell toxicity of these films is lower than the commercially available silver wound dressing.